Formal and Informal Talks of Lecturers in EFL Classroom Interaction - Wahyu Wahyu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aimed to discover the characteristics of formal and informal talks of lecturers in EFL classroom. This research was conducted in qualitative design. Furthermore, the researcher applied discourse analysis under the study of sociolinguistics as an approach to analyze the language, writing, speech, and conversation (verbal and nonverbal) that was appropriate with the purpose of this research. In order to get the data, the researcher did observation and recording. Lastly, the result of the data analysis was presented in description of words, not number. The research was conducted at English Study Program of IAIN Bone.The result shows that the lecturers used formal and informal language. However, the lecturers used formal talk dominantly rather than the informal talk. The characteristic of formal talk which was frequently used by teacher was full form. The teacher frequently used this characteristic in asking question. Whereas informal talk happened frequently when teacher gave explanation particularly in explaining the material. The formal talks which occurred in EFL classroom particularly in student talk consist of four characteristics. They were neutral lexis, full form, politeness phenomena, careful turn taking and title in which using title mostly occurred in interaction among teacher and students. The informal talks which occurred in EFL classroom particularly in student talks were colloquial lexis, interruption/overlapping, first name and nickname, typical mood choice and modal for probability.